The stand [videorecording (DVD)] - Boone, Josh, 1979-; Cavell, Benjamin (Paramount Home Entertainment, 2021)
When a killer plague wipes out 99% of the world's population, the embattled survivors struggle to make their way in a post-apocalyptic reality. This 2020 adaptation of Stephen King's The Stand frames the eternal battle between good and evil, as embodied by the peaceful prophet Mother Abagail and the menacing presence Randall Flagg, and closes with a new coda written by Stephen King himself.